Role of tympanometric volume in paediatric tympanoplasty. Issue 11 (November 2015) - Singh, Gautam Bir; Arora, Rubeena; Garg, Sunil; Ranjan, Shruti; Kumar, Sunil
Abstract Objective To determine the prognostic significance of "Tympaometric Volume" for paediatric tympanoplasty type I in a select age-group of 5–8 years. Methods A prospective study was conducted in 30 children with chronic suppurative otitis media-inactive mucosal disease of either sex. Pre-operative tympanometric volume was recorded in all the cases and statistically analysed with the graft uptake results post-operatively. All the patients underwent tympanoplasty type I by underlay technique using temporalis fascia graft. An intact graft at the end of 6 months, and a postoperative hearing improvement of 10 dB or greater in two consecutive frequencies, was regarded as surgical and audiological success, respectively. The statistical analysis was done using Mantel Haenszel χ2 i.e. Chi square test, and Fisher exact p value test for confirmation. Results We recorded an impressive surgical success rate of 87% and an audiological improvement of 70% in this study. On the basis of mean tympanometric volume of 1.6 cm3 the patients were divided into two groups: in Group A (tympanometric volume < 1.6 cm3), and group B (tympanometric volume > 1.6 cm3). A graft uptake of 95% and 77% was recorded in Group A & B, respectively. However, the statistical evaluation of the data revealed no significant effect of this factor. Conclusions In this study no correlation between the tympanometric volume and the surgical success of paediatric tympanoplasty in select age group of 5–8 years was observed.